Low temperature perovskite solar cells with an evaporated TiO2 compact layer for perovskite silicon tandem solar cells. (September 2017) - Bett, Alexander J.; Schulze, Patricia S.C.; Winkler, Kristina; Gasparetto, Jacopo; Ndione, Paul F.; Bivour, Martin; Hinsch, Andreas; Kohlstädt, Markus; Lee, Seunghun; Mastroianni, Simone; Mundt, Laura E.; Mundus, Markus; et al.
Abstract: Silicon-based tandem solar cells can overcome the efficiency limit of single junction silicon solar cells. Perovskite solar cells are particularly promising as a top cell in monolithic tandem devices due to their rapid development towards high efficiencies, a tunable band gap with a sharp optical absorption edge and a simple production process. In monolithic tandem devices, the perovskite solar cell is deposited directly on the silicon cell, requiring low-temperature processes (< 200°C) to maintain functionality of under-lying layers of the silicon cell in case of highly efficient silicon hetero-junction (SHJ) bottom solar cell. In this work, we present a complete low-temperature process for perovskite solar cells including a mesoporous titanium oxide (TiO2 ) scaffold - a structure yielding the highest efficiencies for single-junction perovskite solar cells. We show that evaporation of the compact TiO2 hole blocking layer and ultra-violet (UV) curing for the mesoporous TiO2 layer allows for good performance, comparable to high-temperature (> 500°C) processes. With both manufacturing routes, we obtain short-circuit current densities (JSC ) of about 20 mA/cm², open-circuit voltages (VOC ) over 1 V, fill factors (FF) between 0.7 and 0.8 and efficiencies (η) of more than 15%. We further show that the evaporated TiO2 layer is suitable for the application in tandem devices. The series resistance of the layer itself and the contact resistance to an indium doped tin oxide (ITO) interconnection layer between the two sub-cells are low. In addition, the low parasitic absorption for wavelengths above the perovskite band gap allow a higher absorption in the silicon bottom solar cell, which is essential to achieve high tandem efficiencies.